Stilistiese analise van nuwe-testamentiese tekste - Floor, L. (Koers, 1986)
All too often literary structures in the New Testament are passed off in scholarly literature as mere literary niceties serving only aesthetic ends. Too little consideration has been given to the possible exegetical signif icance of such structures to the interpretation of biblical texts. This article is an attempt to present an apologetic for the value of stylistic analysis of New Testament texts as an aid in interpreting the New Testament. It must be kept in mind that to the biblical authors, artistry in the use of stylistic structures was not an end in itself, but a means towards more effective communication of the message.